THE USE OF CHLOROPHYLL FLUORESCENCE «a» FOR BIOTESTING OF THE AQUATIC ENVIRONMENT - V. A. Osipov; G. M. Abdurakhmanov; A. A. Gadzhiev; L. B. Bratkovskaya; B. K. Zayadan (Юг России: экология, развитие)
The impact on marine algae Thalassiosiraweisflogii, Pseudo-nitzshiadelicatissima of copper sulfate, chloride of mercury, methylmercury were studied. Found a sharp increase sensitivity FS 2 of microalgae cultures and natural phytoplankton to salts of heavy metals in the conditions of the light of the stress that is associated with inhibition of protein synthetic reactions. Conclusions are made about the prospects of the use of fluorescence of chlorophyll "a" for biotesting.